Analysis of Reproductive Parameters in Sows with Regard to Their Health Status - Pavel Nevrkla; Zdeněk Hadaš; Marie Čechová; Pavel Horký (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The aim of the study was to evaluate selected reproductive parameters in sows. Observed parameters were analysed in two herds with different health status. The experiment involved 160 hybrid sows from the 1st to the 5th litter (80 sows with health status A and 80 sows with health status B). Highly statistically significant differences (P ≤ 0.001) and significant differences (P ≤ 0.05) were found between the two groups in length of gravidity, total numbers of piglets, numbers of live-born piglets, numbers of stillborn piglets, numbers of reared piglets and losses of piglets per litter in favor of group B with declared health status. Evaluation of phenotypic correlation between the total number of piglets and the live-born piglets in the sows without declared health status revealed high positive correlation (P ≤ 0.01). Strong positive dependence was found also between the live-born and the reared piglets in this group. In the sows with declared health status, high positive correlation (P ≤ 0.01) was found also between the total number of piglets and the number of live-born piglets and between the number of live-born and reared piglets.